Model of Development of Future Teachers' Readiness for Professional Activity Based on Acmeological Approach - F.A. Berdibekova (Genius Journals, 2023)
In this article, based on the acmeological approach, the model of development of students' readiness for professional activity is justified. It was discussed about forming the ability and needs of students to constantly update their professional knowledge and skills for creative self-development in order to reach the heights of professional skills.
Keywords: Acmeological approach; professional success; system